Root decomposition of Artemisia halodendron and its effect on soil nitrogen and soil organic carbon in the Horqin Sandy Land, northeastern China. Issue 4 (20th April 2016) - Luo, Yongqing; Zhao, Xueyong; Li, Yuqiang; Zuo, Xiaoan; Lian, Jie; Wang, Tao
Abstract: Root decomposition is a critical feedback from the plant to the soil, especially in sandy land where strong winds remove aboveground litter. As a pioneer shrub in semi‐mobile dunes of the Horqin sandy land, Artemisia halodendron has multiple effects on nutrient capture and the microenvironment. However, its root decomposition has not been studied in terms of its influence on soil organic carbon (SOC) and nitrogen (N). In this study, we buried fine (≤2 mm) and coarse roots in litterbags at a depth of 15 cm below semi‐mobile dunes. We measured the masses remaining and the C and N contents at intervals during 434 days of decomposition. The soils below the litterbags were then divided into layers and sampled to measure the SOC and N contents. After rapid initial decomposition, both coarse and fine roots decomposed slowly. After 53 days, 36.2 % of coarse roots and 39.8 % of fine roots had decomposed. In contrast, only 18.4 % of coarse roots and 30.5 % of fine roots decomposed in the following 381 days. Fine roots decomposed significantly faster, and their decomposition rate after the initial rapid decay was strongly related to climate ( R 2 = 0.716, P < 0.05). Root decomposition increased SOC and N contents below the litterbags, with larger effects for fine roots. The SOC content was more variable between soil layers than the N content. Thus, decomposition of A. halodendron roots cannot be ignored when studying SOC and N feedbacks from plants to the soil, particularly for fine roots.